Terrestrial Fluids, Earthquakes and Volcanoes: The Hiroshi Wakita Volume III - Nemesio M. (Springer, 2017)
Terrestrial fluids, earthquakes and volcanoes: The Hiroshi Wakita volume III is a special publication to honor Professor Hiroshi Wakita for his scientific contribution to science, which has been closely linked with one of the major objectives of this 2008 International Year for the Earth Planet. Reducing natural risks in active tectonic and volcanic environments by searching and detecting early warning hydrological and geochemical signatures related to earthquakes and volcanic eruptions has been a major life research goal for Hiroshi Wakita. This third special issue of Pure and Applied Geophysics consists of 9 original papers written by researchers from Taiwan, Italy, Turkey, Iceland, USA, Sweden, India and Spain dealing with various aspects of the role of terrestrial fluids in earthquake and volcanic processes. It also includes a list of Hiroshi Wakita’s scientific publications. This volume III will be useful to students and professional researchers who are interested in the role of terrestrial fluids in earthquakes and volcanic activity.